Sentiment vs. Fundamentals: GMM Analysis of Jakarta Islamic Index during the 2020–2024 Crisis - Ahmad Yasin; Dewi Cahyani Pangestuti (Master of Management FEB ULM, 2026)
This study examines the impact of macroeconomic (BI Rate, Exchange Rate) and microeconomic factors (Current Ratio, Return on Equity) on the Jakarta Islamic Index (JII) during the 2020–2024 crisis period. Using System Generalized Method of Moments (GMM) on dynamic panel data , the study unexpectedly finds that all selected fundamental variables are statistically insignificant in explaining JII movements. These results indicate a